Purpose of Intracellular Communication Connexin 43 in Breast Cancer Cells - Kadhim, Shahd Abdulamer (International Journal of Psychosocial Rehabilitation, 2020)
Intracellular communication is a vital process that supports cellular activities in both normal breast cells and cancer embedded cells. The procedure is eased by gap junctions; a cluster of aqueous pathways that bond the interior of two neighboring cells. Gap junctions are composed of several connexins that sustain intracellular communication amid adjacent cells. The process entails an exchange of metabolites, ions and electric signals which support cell processes. The channels comprised of connexins support cell to cell association through diffusion. Unlike in normal breast cells, cancer cells have faults in gap junctions, caused by poorly expressed connexins. While there exists several types of connexins, connexin 43 is a special gap junction that functions independently and plays integral roles as far as intracellular communication amid cancerous cells is concerned. Such roles include gene transcription and signal transduction. As such, connexin 43 is associated with breast cancer pathogenesis. Based on the above findings, this paper highlights the major roles of gap junctions and connexin 43 intracellular communication, particularly in breast cancer development. Moreover, connexin 43 also enhances metastasis and invasion which are vital in cancer cell dormancy and regeneration of cancer stem cells. Therefore, the paper also features inclusive knowledge regarding functional dynamics and discrepancy expression of connexin 43 the pathogenesis of breast cancer.